Factors influencing the decision to use hanging as a method of suicide: qualitative study. - Biddle, L; Donovan, J; Owen-Smith, A; Potokar, J; Longson, D; Hawton, K; Kapur, N; Gunnell, D (2010)
BACKGROUND: Hanging is the most frequently used method of suicide in the UK and has high case fatality (>70%). AIMS: To explore factors influencing the decision to use hanging. METHOD: Semi-structured qualitative interviews with 12 men and 10 women who had survived a near-fatal suicide attempt. Eight respondents had attempted hanging. Data were analysed thematically and with constant comparison. RESULTS: Hanging was adopted or contemplated for two main reasons: the anticipated nature of a death from hanging; and accessibility. Those favouring hanging anticipated a certain, rapid and painless death with little awareness of dying and believed it was a 'clean' method that would not damage the body or leave harrowing images for others. Materials for hanging were easily accessed and respondents considered it 'simple' to perform without the need for planning or technical knowledge. Hanging was thus seen as the 'quickest' and 'easiest' method with few barriers to completion and sometimes adopted despite not being a first choice. Respondents who rejected hanging recognised it could be slow, painful and 'messy', and thought technical knowledge was needed for implementation. CONCLUSIONS: Prevention strategies should focus on countering perceptions of hanging as a clean, painless and rapid method that is easily implemented. However, care is needed in the delivery of such messages as some individuals could gain information that might facilitate fatal implementation. Detailed research needs to focus on developing and evaluating interventions that can manage this tension.